ARCHITECTONICS OF ‘AUSTERLITZ’, A NOVEL BY W. G. SEBALD - Megela , Ivan (PROBLEMS OF SEMANTICS, PRAGMATICS AND COGNITIVE LINGUISTICS, 2022)
The article describes the problems of architectonics as the main construction principle of Austerlitz, a novel by German author W. G. Sebald. The aim of this article is to analyze architectonics as a general system of connections between separate parts of the artistic whole, as well as an artistic discourse that organizes the interaction between the aesthetic subject, aesthetic object and aesthetic addressee through cohesion and coherence of elements of different levels of the text. The article describes the essence of the concept of time in the novel; each moment can be revisited both at the level of reminiscence and inner feeling. The concept of time is subordinate to the character’s pursuit – unraveling the mystery of his real ancestry and the way of exploring personal history in forgotten locations, cities and streets of lost time, in a phantom happy childhood. The article examines the formation of artistic space from the character’s past, his travels down the memory lane; from flashbacks, dialogues between Jacques Austerlitz and the nameless listener (narrator, in fact, the author ofthe work); from descriptions of architectural structures, penitentiaries, fortresses, castles; from black-and-white photographs of various objects, objects that give the text the authenticity of a chronicle. Austerlitz rejects the documentary – fiction dichotomy cannot be unambiguously defined either as fiction or as a historical work. The article argues that this is the literature of personal experience ‘from the other side’, when the theme of memory and destruction reveals itself not through established historical symbols, but through personal dialogue between man and the material world.The article argues that this is the literature of personal experience ‘from the other side’, when the theme of memory and destruction reveals itself not through established historical symbols, but through personal dialogue between man and the material world.The analysis concluded that the architectonics in Austerlitz functions as series of consecutive moral problems associated with individual guilt about historical events. It is a dense intertextual postmodern documentary-fiction novel in which the author's experience is combined with emotions, personal empathy, synesthesia, which separates him from the official interpretation of history, coverage of painful problems of the past (Holocaust), trauma and oblivion.__________References:• De Beaugrande, Robert; Dressler, Wolfgang. Introduction to Text Linguistics (New York, 1996): 84-112.• Domashhenko,A. V. Ob interpretacii i tolkovanii: monografija (Doneck: DonNU, 2007), 277.• Topographies of Memory in WG Sebald's Austerlitz, https://scholarworks.utep.edu › cgi › viewcontent• Memory and Amnesia in WG Sebald's Anti-narrative, https://scholars.wlu.ca › cgi› viewcontent • Exploring the Edge of Trauma in W.G. Sebald's Novel 'Austerlitz', https://d-nb.info › ...• How History is Presented in Sebald's Austerlitz, https://wordpress.viu.ca › how...• Bahtin, M. M. «Problema soderzhanija, materiala i formy v slovesnom hudozhestvennom tvorchestve.» Voprosy literatury i jestetiki (Moskva: Hudozh. lit., 1975), 502.• Val'cel', O. Problema formy v pojezii (Academia, 1923), http://www.opojaz.ru › walzel › walzel• Tjupa, V. I. «Literaturnoe proizvedenie: mezhdu tekstom i smyslom.» Literaturnoe proizvedenie: problemy teorii i analiza 1 (Kemerovo: Kuzbassvuzizdat, 1997): 3-78.• Zebal'd, V. Austerlic (Kyi'v: Komubuk, 2020), 336.• Jaggi, Maya. “Recovered Memories.” The Guardian (21 Sept. 2001), https://www.the guardian.com/books/2001/sep/22/artsandhumanities.highereducation• Jonny Begood, https://jonny-begood.livejournal.com • The Aesthetics and Ethics of Refraction: Narrative Structure... , http://dspace.library.uvic.ca › bitstream › handle • Megela, I. P. «Metamorfozy zhanru:psyhograma serijnogo vbyvci (na materiali romanu «Tysha» Tomasa Raaba». Problemy semantyky, pragmatyky ta kognityvnoi' lingvistyky 33 (2018): 60-70.• Megela, I. P. «Pryncypy smyslotvorennja us filosofs'kij kazci Germana Gesse «Peretvorennja Piktora». Problemy semantyky, pragmatyky ta kognityvnoi' lingvistyky 35 (2019): 45-59.• Megela, I. P. «Polityka i moral' v romani Roberta Menasse «Stolycja»». Problemy semantyky, pragmatyky ta kognityvnoi' lingvistyky 39 (2021):43-60.• Writing as Ethical Memory in "Austerlitz" – JSTOR, https://www.jstor.org › stable• Vertigo | Where literature and art intersect, with an emphasis... , https://sebald.wordpress.com
Keywords: architectonics, structure, story, time, documentary, fiction, memory, trauma, oblivion, architecture, photography, reminiscence, empathy, synesthesia